Strengthening Competency-Based Human Resource Training and Development Systems (A Study of the Kartika Job Training Institute) - Duha, Efitahati; Dewi, Idah Kusuma (Journal Research of Social Science, Economics, and Management, 2026)
Human resources (HR) are seen as a key factor in determining the success of an organization, including job training institutions which have a strategic function in preparing a competent workforce ready to enter the world of work. This study aims to analyze the strengthening of a competency-based training and human resource development system at Kartika Bawen Training Center (LPK Kartika-Bawen). The research focuses on how the training system is designed, implemented, and evaluated to support the achievement of trainees’ competencies in accordance with the Indonesian National Work Competency Standards (SKKNI). A descriptive qualitative approach was employed to obtain an in-depth and contextual understanding of actual training practices, existing challenges, and sustainable strengthening strategies. Data were collected through in-depth interviews, direct observation, and document analysis involving purposively selected informants, including institutional leaders, instructors, administrative staff, and training participants. The findings indicate that although the training system at LPK Kartika Bawen has referred to SKKNI, its implementation has not been fully optimized. Key challenges include limited instructor competence in utilizing learning technologies, infrequent curriculum updates, predominantly conventional learning methods, inadequate training facilities, and the absence of a comprehensive training evaluation system. This study recommends an integrated approach to strengthening the training system through continuous development of internal human resources, curriculum renewal, learning method innovation, modernization of training facilities, and the application of the four-level Kirkpatrick evaluation model to enhance graduates’ competency relevance and workforce competitiveness in a sustainable manner.